Α-MnO2/MWCNTs as an electrocatalyst for rechargeable relatively closed system Li–O2 batteries. Issue 89 (26th October 2021) - Wu, Min; Liu, Dechong; Li, Zhuxin; Tang, Yu; Ding, Yajun; Li, Yuejiao; Wu, Zhong-Shuai; Zhao, Hong
Abstract : The RCLO battery that requires no extra O2 to be introduced into the reaction system during the reaction processes. Abstract : Herein, a new, relatively closed system Li–O2 (RCLO) battery, without extra oxygen being involved in the reaction during the charge and discharge process, is reported. This relatively closed system effectively solves the key issue of poor circulation caused by oxygen generation in conventional Li–O2 batteries.